2020
DOI: 10.1016/j.ygyno.2020.06.481
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal hormone therapy prior to the diagnosis of ovarian cancer is associated with improved survival

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.typesetting and review before it is published in it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 37 publications
2
34
2
Order By: Relevance
“…Several other studies have suggested that menopausal hormone use may be associated with improved ovarian cancer survival [36] , [37] , [38] , [39] , but we found no such association, nor did the NIH-AARP study [40] . We found little or no evidence of an association between ovarian cancer survival and other reproductive or hormonal factors, broadly in keeping with previous reports [37] .…”
Section: Discussioncontrasting
confidence: 97%
“…Several other studies have suggested that menopausal hormone use may be associated with improved ovarian cancer survival [36] , [37] , [38] , [39] , but we found no such association, nor did the NIH-AARP study [40] . We found little or no evidence of an association between ovarian cancer survival and other reproductive or hormonal factors, broadly in keeping with previous reports [37] .…”
Section: Discussioncontrasting
confidence: 97%
“…However, among women with a historyAU : IntheDiscusion; Ichangedallinstancesof xxxcancersurvivorstowomenw of breast or ovarian cancer, pre-or post-diagnosis MHT use was associated with improved cancer-specific or overall survival. The findings were further replicated by 2 recent prospective cohort studies [114,115]. One possible explanation for these findings could be that women who used MHT after diagnosis were likely to have used MHT before diagnosis.…”
Section: Breast and Ovarian Cancermentioning
confidence: 58%
“…One possible explanation for these findings could be that women who used MHT after diagnosis were likely to have used MHT before diagnosis. Therefore, despite increased incidence of breast and ovarian cancer with MHT use, MHT users with established breast and ovarian tumors may have better prognosis than nonusers [ 114 , 115 ]. Observational data on MHT and breast cancer mortality were controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve prediagnosis exposures of interest were included in this analysis: lifetime alcohol use, aspirin use, other nonsteroidal antiinflammatory drug (NSAID) use, BMI, environmental smoke exposure (ever having been exposed to smoking in the home or at work as defined by each study), history of pelvic inflammatory disease (PID), polycystic ovarian syndrome (PCOS), endometriosis, MHT use, physical inactivity, smoking status, and talc use. Details on the definitions of the exposures have been described elsewhere (5,(27)(28)(29)(30)(31)(32) and are presented in Supplementary Table S1. Within each OCAC study, the pattern of missingness among these exposures was investigated.…”
Section: Methodsmentioning
confidence: 99%